Psychodiagnosis Program for Persons Deprived of Liberty: Array - Popa, Ecaterina; Iurсheviсi, Iuliа (Journal of Danubian Studies and Research, 2020)
This article aims to develop and experimentally validate a psychodiagnostic program for persons deprived of liberty, which provides clear directions for recommending psychosocial programs so as to ensure that positive behavioral changes are observed after completing them. Furthermore, this study focuses on highlighting the importance of developing a psychodiagnostic program for incarcerated people to establish more effective methods of intervention and inclusion in various psychosocial programs that contribute effectively to their behavioral change.